Burnout among the non-government secondary school teachers in Bangladesh: Prevalence, causes and effects - Roy, Bijon Kumar; Jony, Md. Solaiman; Rabbi, Md. Fajlay (Journal of Research in Instructional, 2024)
Nowadays, psychological burnout is prevalent in all professions. The purpose of this study is to investigate the prevalence, causes, and consequences of burnout among non-government school teachers in Panchagarh. This study used an explanatory sequential mixed approach. A stratified random selection methodology was employed to pick 25 schools, and 242 teachers were chosen using a simple random sample procedure. Finally, a purposive sample technique was used to select 15 teachers. Data was acquired using a standardized questionnaire and in-depth interviews. The Maslach Burnout Inventory-Educator Survey (MBI-ES) was used to assess the prevalence of burnout. Data was analyzed by descriptive statistics and thematic analyses. The study found a high prevalence of burnout in non-government school teachers in Panchagarh, with 48.35% experiencing high emotional exhaustion, 51.24% high depersonalization, and 45.04% low personal accomplishment. Also, the study found that low salary are the most contributing factor to burnout. Furthermore, 78.6% of respondents agreed that teacher burnout has negative effects on student academic achievement. Finally, the presence of teacher burnout in education is a challenging issue, as it negatively affects every aspect of the learning and teaching process. This study has implications for policymakers to develop plans to reduce teacher burnout and enhance teachers’ overall well-being.